Learning and Age-Related Changes in Genome-wide H2A.Z Binding in the Mouse Hippocampus - Stefanelli, Gilda; Azam, Amber B.; Walters, Brandon J.; Brimble, Mark A.; Gettens, Caroline P.; Bouchard-Cannon, Pascale; Cheng, Hai-Ying M.; Davidoff, Andrew M.; Narkaj, Klotilda; Day, Jeremy J.; Kennedy, Andrew J.; Zovkic, Iva B. (Cell reports (Cambridge), 2018)
Histone variants were recently discovered to regulate neural plasticity, with H2A.Z emerging as a memory suppressor. Using whole-genome sequencing of the mouse hippocampus, we show that basal H2A.Z occupancy is positively associated with steady-state transcription, whereas learning-induced H2A.Z removal is associated with learning-induced gene expression. AAV-mediated H2A.Z depletion enhanced fear memory and resulted in gene-specific alterations of learning-induced transcription, reinforcing the role of H2A.Z as a memory suppressor. H2A.Z accumulated with age, although it remained sensitive to learning-induced eviction. Learning-related H2A.Z removal occurred at largely distinct genes in young versus aged mice, suggesting that H2A.Z is subject to regulatory shifts in the aged brain despite similar memory performance. When combined with prior evidence of H3.3 accumulation in neurons, our data suggest that nucleosome composition in the brain is reorganized with age. [Display omitted] •The histone variant H2A.Z accumulates with age in the mouse hippocampus•H2A.Z is evicted in response to learning, irrespective of age•H2A.Z is altered on distinct genes in young and aged mice•H2A.Z eviction from promoters and genes is associated with increased transcription Stefanelli et al. find that the histone variant H2A.Z accumulates with age in the hippocampus and that learning results in H2A.Z removal from distinct genes in young and aged mice despite similar levels of memory formation. These data suggest that replication-independent histone variants become overrepresented in neural chromatin during aging.